Development of IoT at hydroponic system using raspberry Pi - Rony Baskoro Lukito; Cahya Lukito (Universitas Ahmad Dahlan, 2019)
Hydroponics is one of the farming technologies using water media to meet the needs of plant nutrition. Water use in hydroponics systems more efficient compared with the cultivation system using soil media. Water that has been mixed with mineral nutrients needed by plants streamed continuously to the plant roots. Another advantage of this method is very suitable to be applied in a limited area such as urban home environments, the use of the existing space in the house. In the everyday activities of urban residents spending more time outside the home to work, school, shopping and other activities. Thus the observation of hydroponic systems remotely be important to be done from anywhere. Availability, temperature, and pH of the water are some of the factors in hydroponic systems that need to be observed periodically to determine the appropriate action. This problem can be solved by developing the Internet of Things technology in the hydroponic system that observations can be done remotely and reported directly through the Internet.